Estimating the Coefficients of Polynomial Regression Model when the Error Distributed Generalized Logistic with Three Parameters - Ahmed, Ahmed Dheyab; Abdulah, Ebtisam Karim; Abdulwahhab, Baydaa Ismael (International Journal of Psychosocial Rehabilitation, 2020)
-In this research, estimates of polynomial regression model coefficients are derived when the random error is logistically distributed with three parameters representing scale, shape and location. By employing simulation method, the model coefficients are compared using methods of General Least Squares and the modified maximum likelihood. Based on statistical criteria, the Mean Square Error (MSE) indicated that the modified maximum likelihood (MML1) method is the best. This method is applied to data of Gross Domestic Product (GDP) at current prices in Iraq.